PERAN PERSEPSI HARGA DALAM MEMODERASI PENGARUH PENGETAHUAN TENTANG PRODUK TERHADAP NIAT BELI PRODUK RAMAH LINGKUNGAN MEREK TOYOTA AGYA - Dewi Indrawati, Kadek; Suparna, Gede (E-Jurnal Manajemen, 2015)
This study aims to investigate the influence of product knowledge and price perception of the consumer's purchase intention, and role in moderating the price perception of product knowledge to the consumer's purchase intention. The sample was determined by purposive sampling, the sample size of 110 respondents to the survey method using a questionnaire measured with Likert scale, analytical techniques using MRA (Moderated Regression Analysis). The results showed product knowledge significant positive influence on consumer purchase intention. Perception of price significant positively effect on purchase intention, and perception can become a moderating variable price, but weaken the influence of knowledge about the product to the consumer's purchase intention.
Keywords: product knowledge, price perception, purchase intention to environmentally products.